Dernier refuge ou presqu'île d'opportunités? Démographie et conditions de vie à Adjahui-Coubé, un habitat spontané à Abidjan - Irit Eguavoen; Pauline Attemene; Fulgence Kouame; Eugène Kouadio Konan; Chérif Aidara Madhy; Katrin Gleisberg-Gerber (University of Bonn, Center for Development Research (ZEF), 2020)
– This research report summarises findings from an ethnographic census, interviews and observations on an Ebrié village within the metropolis of Abidjan, which has undergone a process of rapid, unplanned and irreversible urbanisation since 2012. The study estimates the population number in mid-2018 to stand at 60 000 inhabitants minimum. The visual, qualitative and quantitative data set includes the documentation of 52 courtyards and 591 housing units. The main driver of spontaneous urbanisation in the beginning was finding any housing after having been forcefully evicted from the former place of residence. Many of these people originated from families who had migrated to the Côte d'Ivoire from ECOWAS. In a second phase, the population became more Ivorian including many poor families and young people who were excluded from rental housing in precarious quarters of Abidjan because of decreased availability and affordability. Finally, the purchasing power of the growing population and the construction boom became economic pull factors to the village. The report documents the evolution of the settlement within its historical, legal and political context and analyses living conditions and some strategies of the inhabitants and authorities.
Keywords: 330; housing; slum; forceful eviction; urbanisation; Africa